Social and cultural pain: his narrative in relation to the other - Bernal, Patricia (InMediaciones de la Comunicación, 2016)
I intend to focus here on the issue of social and cultural pain from four different perspectives of analysis. First, I will refer to the dualism between the material and the spiritual, in order to understand some ontological aspects that derive from such opposition. On a second moment, I will discuss pain in some of its cultural dimensions. The third perspective will consider pain as something that is caracteristically humane. Finally, I will discuss pain and its relation with the Other. (Complete article in spanish language).